Uncovering the cellular diversity of Fasciola hepatica utilizing single-cell transcriptomics - Puckelwaldt, Oliver; Justus Liebig University Giessen (My University, 2024)
The liver fluke Fasciola hepatica is a widespread parasite affecting humans and animals. It causes considerable economic loss by infecting livestock. The World Health Organization also recognizes fasciolosis as a neglected tropical disease. Successful treatment of the disease heavily relies on the drug triclabendazole, and the widespread development of resistance makes the discovery of new treatment strategies essential. Transcriptome analysis has the potential to reveal fundamental aspects of parasite biology and identify new drug targets. By design, classical RNAseq methods analyze gene expression of a mixture of various cells, which can thus only deliver transcriptome information of tissues or entire organisms without discrimination of different cell types. New technologies allow the analysis of the transcriptome of individual cells. This information gives scientists a new perspective for research on previously neglected organisms. This work aimed to establish and characterize a single-cell transcriptome dataset for the liver fluke F. hepatica. For this purpose, a method for isolating and enriching cells from the adult parasite stage using the protease trypsin was established. Cellular composition, quality, and RNA integrity were optimized for transcriptome analysis. In addition, the fixation of cells with acidic methanol was identified as useful approach to preserve cells for transportation and later analysis. Single-cell transcriptome analysis using the 10x Chromium technology was performed with separately dissociated anterior and posterior parts of the liver fluke to enrich for rare cells. A total of 15 cell clusters over 19,581 cells were identified and 8716 genes were expressed. Among the identified clusters were cells of the reproductive organs, including testes (4 clusters), ovary (2 clusters), vitellarium (2 clusters), and one cluster representing cells of the Mehlis‘ gland. Furthermore, stem cells, muscle cells, cells of the gastrodermis, and a previously unknown cell population named elf5+ due to the expression of an ETS transcription factor were identified. Marker genes were determined for the identified cells and verified for selected cell types using RNA in situ hybridization. These marker genes included a phospholipase-B-like gene previously unrecognized as a gene expressed in the gastrodermis, which might have implications for immunosuppression of the liver fluke in the final host. Classical markers like tektin for the male gem cells or the classical muscle markers myosin and collagen were verified. Gene ontology analysis with transcriptional markers of the clusters allowed a functional characterization of the clusters, allowing for a better distinction between differentiated and proliferating cells. A joint approach of gene ontology analysis with STRING analysis was used to characterize signal transduction networks in both female germ cells and the elf5+ cluster. Leveraging this approach led to the identification of a signaling network, including the kinase p38, that might be involved infemale germ-cell function or enrichment for focal adhesion signaling in the elf5+ cluster. Furthermore, an RNA velocity analysis indicated a differentiation lineage of the vitellocytes. Two lineages were predicted over five subclusters. One lineage included clusters characterized by expression of the histone 2b and a nuclear receptor named Vf1 and was annotated as S1 vitelline cells reentering the cell cycle, while a second lineage over clusters with marked expression of two tyrosinases was assigned to maturing vitellocytes. Finally, the dataset's utility for discovering new treatment strategies was demonstrated. The newly described elf5+ cell cluster was identified as promising for drug discovery based on preferential transcription of an orthologue of the previously described drug target of praziquantel, FhTRPMPZQ. Interest was focused on the specific expression of various protein kinases in this cell cluster. The p21-activated kinase PAK4 was tested for its potential as a drug target using the inhibitor LCH-7749944. The inhibitor significantly affected all life stages of the liver fluke that are found in the final host when exposed in vitro to concentrations of 25 to 50 μM. Preliminary data also suggested the activity of LCH-7749944 against related flatworm species. This confirms the utility of the F. hepatica single-cell data as a basis for drug discovery. In summary, the first transcriptional characterization of single cells from liver flukes was achieved. A method for isolating liver fluke cells and adapting the technique to the worm's anatomical characteristics led to the first description of important cell types. This data set represents an important resource for the fundamental understanding of liver flukes and may facilitate the discovery of new active substances.
Keywords: ddc:570